Microlite offered free-choice to growing-finishing pigs - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Growing and finishing pigs consumed from 54 to 64 grams of Microlite per head per day when it was available free choice from a self-feeder. It had no measurable affect on average daily gain, feed consumption, feed efficiency, or behavior of pigs eating a complete ration.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Microlite; Growing pigs; Finishing pigs